Crude oil bioremediation by indigenous bacteria isolated from oily sludge - Azizan, Nur Hafizah; Apun, Kasing; Bilung, Lesley Maurice; Vincent, Micky; Roslan, Hairul Azman; Awang Ahmad Husaini, Awang Ahmad Sallehin (UTM Press, 2016)
Enrichment culture technique leads to the discovery of six presumptive TPH-degrading bacteria. Identification and characterization tests using morphological, biochemical and molecular techniques have successfully isolated Pseudomonas aeruginosa (UMAS1PF), Serratia marcescens (UMAS2SF) and Klebsiella spp. (UMAS3KF). All strains were able to use crude oil as sole carbon and energy source for their growth since they were able to survive in Minimal Salt medium supplemented with 1% (v/v) crude oil. Growth study showed that they produced the highest cell counts on the third or fourth day by 108 – 1011 CFU/ml. Six artificial consortium inoculums have been produced from the growth study. Gas chromatography analysis showed that all isolates had the ability to degrade aliphatic hydrocarbon with 100% degradation of nC19 – C24. Among the isolates, UMAS2SF was the best and fastest n-alkane degrader with degradation percentage between 55 – 90% of n-C14 – C18 in 14 days. This was followed by UMAS1PF and UMAS3KF with 11 – 82% and 1.3% degradation, respectively. Enhancement study showed that plot with inoculum and NPK addition successfully enhanced n-alkane degradation. Plot A2:B3+NPK degraded n-alkane the fastest followed by plot treated by C+NPK, A1:B2, B+NPK and A2:B3. Result showed that UMAS1PF was the best PAHs degrader as most of the high molecular weight PAHs was degraded. In the enhancement study, the plot amended with A2:B3 showed the highest PAHs degradation, followed by plots A1:B2, A3:B1:C2 and A1:C3 that was assigned as the third, fourth and fifth best in mineralizing PAHs, respectively.